2013
DOI: 10.5935/1676-4285.20133876
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about diabetes in patients hospitalized for heart disease: a descriptive research

Abstract: Aim: To assess the knowledge of patients hospitalized for cardiovascular co-morbidities in diabetes mellitus (DM), and its relationship to the confrontation and attitudes towards the disease. Method: This was a prospective cross-sectional study, conducted in the inpatient unit with cardiac patients affected by DM. Their level of knowledge about diabetes was assessed using the Diabetes Knowledge Scale (DKN-A) and the psychological and emotional aspects were assessed by use of the Diabetes Attitudes Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
2
4
0
1
Order By: Relevance
“…The time of diagnosis of DM was greater than 10 years in 46.30% of the patients, as well as in other studies (SILVA et al, 2013;SNOEK et al, 2000). Pace et al (2006) studied 659 patients with DM2, most of them were men and the average disease time was greater than ten years.…”
Section: Discussionsupporting
confidence: 80%
“…The time of diagnosis of DM was greater than 10 years in 46.30% of the patients, as well as in other studies (SILVA et al, 2013;SNOEK et al, 2000). Pace et al (2006) studied 659 patients with DM2, most of them were men and the average disease time was greater than ten years.…”
Section: Discussionsupporting
confidence: 80%
“…The lack of knowledge of the term ketone may be related to the lack of use of this word in the daily dialogue between health professionals and people with diabetes, which is translated by the difficulty of interpreting the word by the elderly interviewed. A study performed with individuals with diabetes and cardiopathy obtained a similar result when evaluating the main questions related to self-care, among which, besides ketonuria, hypoglycemia management obtained a lower score 20 . In this casuistry, the results are even more of concern, since most of the respondents are unaware of the management of hypoglycemia and do not know how to identify the causes of its occurrence.…”
Section: Discussionmentioning
confidence: 62%
“…Other research found that, regarding behavior, the scores ranged from 25 to 71, suggesting difficulty in coping with the disease (10) . There is a need for the development of programs and educational strategies that provide a learning space for the individual (13) . In this context, the school plays an important role in the formation of healthy habits on the part of adolescents (14) .…”
Section: Discussionmentioning
confidence: 99%